Gut microbiota-derived metabolites: implications for metabolic syndrome and therapeutic interventions - Samuel Oluwadare Olalekan; Olalekan Olanrewaju Bakare; Ifabunmi Oduyemi Osonuga; Abayomi Samson Faponle; Bukunola Oluyemisi Adegbesan; Esther Nkechi Ezima (SpringerOpen, 2024)
Abstract Background The gut microbiota (GM) and their metabolites have garnered significant attention for their roles in metabolic syndrome (MetS) and associated conditions. MetS, characterized by a cluster of metabolic abnormalities, significantly increases the risk of cardiovascular disease (CVD), obesity, insulin resistance, and type 2 diabetes mellitus (T2DM). The dysbiosis of gut microbiota, marked by changes in microbial composition and function, has been implicated in the pathogenesis of MetS. Main body This review synthesizes recent findings elucidating the influence of GM composition and microbiota-derived metabolites on MetS pathogenesis and progression. Notably, alterations in GM composition and dysregulation of metabolites such as short-chain fatty acids (SCFAs), trimethylamine N-oxide (TMAO), polyamines, amino acids, and indole derivatives have been implicated in MetS development. These metabolites play crucial roles in metabolic processes, and their imbalance can trigger or exacerbate metabolic disturbances associated with MetS. Various therapeutic approaches, including dietary interventions, probiotics, prebiotics, and precision medicine targeting specific metabolites, offer promising strategies for managing MetS. These interventions aim to restore a healthy GM balance and regulate the production of beneficial metabolites. Conclusion The complexity of GM interactions and their systemic effects necessitate more standardized research methodologies. Future investigations focusing on personalized therapeutic interventions and non-invasive diagnostic tools are warranted to address the complexities of MetS management. Advancing our understanding of the GM-metabolite-MetS axis will be crucial for developing effective, targeted treatments and improving patient outcomes in MetS.